EPID-06. IMMUNE-RELATED PLASMA BIOMARKERS IN GLIOBLASTOMA. (11th November 2019) - Bjørnbak Holst, Camilla; Jarle Christensen, Ib; Skjoeth-Rasmussen, Jane; Skovgaard Poulsen, Hans; Hamerlik, Petra; Sidenius Johansen, Julia
Abstract: BACKGROUND: Glioblastoma (GBM) is an aggressive and malignant primary brain tumor with limited treatment options and a dismal prognosis. Immunotherapy is advancing in other types of cancer but has not yet proven effective in glioblastoma. Prognostic and predictive biomarkers and new treatment targets are urgently needed. MATERIAL AND METHODS: 158 patients with glioma WHO grade II-IV were included in the study. Plasma was analyzed for interleukin (IL)-6, YKL-40 (Gene: CHI3L1 ) and 91 other immune-related protein biomarkers by ELISA or/and Olink technology. CHI3L1 rs4950928 genotyping was analyzed on DNA extracted from whole-blood. RESULTS: Fourteen of 92 immune-related biomarkers in plasma detected with the Olink immuno-oncology array were related with tumor grade or/and type (p< 0.05) (corrected for age), whereas plasma IL-6 and YKL-40 did not change with tumor grade. In univariate analysis of plasma from 94 patients with newly diagnosed GBM higher baseline IL-6 was associated with short OS (HR=1.19 (per 2-fold change in IL-6), p=0.04), YKL-40 showed a similar trend (HR=1.20 (per 2-fold change in YKL-40), p=0.056) and high/low baseline levels of additional 15 immune-related biomarkers (e.g. CD244, Granzyme B, ICOS ligand, IL-8 and Pleiotrophin) were associated with short OS (p< 0.05). Genetic variation in YKL-40 was associated with plasma YKL-40 levels (+/+ vs. -/+ vs. -/-, p=0.0004) but not with OS in patients with GBM (HR= 0.78 (+/+ vs. -/+), p=0.32). CONCLUSION: High levels of several immune-related biomarkers in plasma including IL-6, IL-8, CD244, Granzyme B, ICOS ligand, and Pleiotrophin from patients with glioblastoma were related or inversely related to OS.